Label-free selective detection of ampicillin drug in human urine samples using silver nanoparticles as a colorimetric sensing probe. (20th June 2017) - Shrivas, Kamlesh; Sahu, Jharna; Maji, Pathik; Sinha, Deepak
Abstract : Stable citrate-capped silver nanoparticles (AgNPs) were developed as a colorimetric sensing probe for selective detection of ampicillin in urine samples. Abstract : Stable citrate-capped silver nanoparticles (AgNPs) were developed as a colorimetric sensing probe for selective detection of ampicillin in urine samples. The method is based on the color change from yellow-to-pink and a red shift of localized surface plasmon resonance (LSPR) absorption band of AgNPs in UV-Vis region after the addition of ampicillin into the NPs solution. This is due to the aggregation of AgNPs induced via the replacement of citrate stabilizing molecules from the surface of NPs by hydrolyzed product of ampicillin (penicillamine) formed at pH 4.0 through Ag–sulfur binding and electrostatic force of interactions. The control experiments were also carried out in those drugs that were not hydrolyzed and had no sulfur entity. They did not exhibit any color change and red shift of LSPR in UV-Vis region. The linear range for determination of ampicillin was found in the range of 25–1200 ng mL −1 with their limit of detection being 10 ng mL −1 . In comparison to conventional spectrophotometric and sophisticated analytical instruments, the proposed method was found to be simple, sensitive and cost effective for the determination of ampicillin in urine samples.